2011
DOI: 10.1088/1475-7516/2011/08/023
|View full text |Cite
|
Sign up to set email alerts
|

Probing bulk viscous matter-dominated models with gamma-ray bursts

Abstract: In this paper we extend the range of consistency of a constant bulk viscosity model to redshifts up to z ∼ 8.1. In this model the dark sector of the cosmic substratum is a viscous fluid with pressure p = −ζθ, where θ is the fluid-expansion scalar and ζ is the coefficient of bulk viscosity. Using the sample of 59 high-redshift GRBs reported by Wei (2010), we calibrate GRBs at low redshifts with the Union 2 sample of SNe Ia, avoiding then the circularity problem. Testing the constant bulk viscosity model with GR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 79 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…4 we see that dark structures are severely suppressed for the valueξ = 1.5. Note that in this case the background expansion is not accelerated [23][24][25][26]. The dissipative mechanism present in the bulk viscous fluid avoids the formation of viscous dark matter halos in the unified scenario.…”
Section: B Bulk Viscous Fluidmentioning
confidence: 99%
“…4 we see that dark structures are severely suppressed for the valueξ = 1.5. Note that in this case the background expansion is not accelerated [23][24][25][26]. The dissipative mechanism present in the bulk viscous fluid avoids the formation of viscous dark matter halos in the unified scenario.…”
Section: B Bulk Viscous Fluidmentioning
confidence: 99%
“…Indeed, an update has been made recently of the sample of GRBs now consisting of 109 objects [32]. In [32,33] new calibrations have been developed in order to use GRBs in cosmological tasks.…”
Section: Grbs: Wang 2008 Data Setmentioning
confidence: 99%
“…The dark energy phenomenon as an effect of the bulk viscosity in the cosmic medium has been first investigated in [48]. All these cited works are pioneer papers on the cosmological bulk viscosity, but it is also worth noting some recent applications of viscous fluids as candidates for dark matter [49], dark energy [50][51][52][53][54] or unified models [55][56][57][58][59][60], i.e., when a single substance plays the role of both dark matter and dark energy simultaneously. Indeed, it has been shown that for an appropriate viscosity coefficient, an accelerating cosmology can be achieved without the need of a cosmological constant [61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%